Imaging Technologies in Breast Cancer Screening Beyond Mammography - Singh, Shamy; Dheeba, J. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
Still there is a passionate debate in medical world about the best screening method for Breast Cancer. Early detection is an effective way to diagnose and manage breast cancer. Mammography is the most widely used screening modality, with solid evidence of benefit for women aged 40 to 74 years. Even then it has also undergone increased scrutiny for False-Positives with additional testing which increase radiation dose, cost and anxiety. False-Negatives with false sense of security and potential delay in cancer diagnosis. To overcome these challenges, new imaging technologies for breast cancer screening have been developed, including; X- ray Mammography, Contrast Enhanced Mammography, Digital Mammography, Ultrasound, Automated Whole Breast Ultrasound (AWBU), and Magnetic Resonance Imaging (MRI) are being evaluated. The purpose of this paper is to provide an overview of different medical imaging techniques used in the diagnosis of breast cancer. We compare their effectiveness, advantages, and disadvantages for detecting early-stage breast cancer. We mainly focusing on the comparison of these technologies with mammography for the diagnosis of breast cancer. Here we recommend Digital Mammography is the best available screening method for the early detection of Breast Cancer. Even though the optimal screening will ultimately require a personalized approach. It based on the metrics of cancer risk with selective application of specific screening technologies best suited to the individual’s age, risk, and breast density.